COVID-19, agricultural production, and food value chains - Place, Frank; Stoian, Dietmar; Minot, Nicholas (International Food Policy Research Institute, 2022)
Over the course of the pandemic, research on how COVID-19 has affected agricultural production and food value chains has evolved: as coronavirus infection rates rose and fell and governments instituted a range of responses, the research focus shifted from projecting what might happen to reflecting on what did happen. Early studies focused on the immediate effects of the lockdowns and other restrictions on food supplies. Later studies began to delve more deeply into the diverse private and public countervailing responses — as governments sought to offset the negative impacts of lockdowns — and their effectiveness in maintaining food supply and demand. The growing number of relatively high-quality studies on agriculture and food supply chains allows for some assessment of factors that appear to have diminished or aggravated the impacts of the pandemic. The analytical framework and the methodology used to develop our findings are summarized in Box 1.